(Mis)performance in classical Croatian experimental cinema - Gilić, Nikica (2009)
The historical insight in Croatian experimental film and video shows how the process of mainstreaming the conceptual art and performance governs both the reception of contemporary art and its creation.From Mihovil Pansini's experimental films from the 1960s and Sanja Iveković video-performances from the 1970s and 1980s to the present day art, the conceptual and radically modernist art slowly became more and more central to the art scene.
Projekt MZOS
ENG